Báo cáo giải trình, tiếp thu ý kiến thẩm định của Bộ Tư pháp đối với dự án Luật giá (sửa đổi) (Số: 115/BC-BTC) - Bộ Tài chính (2022)
Toàn văn Báo cáo giải trình, tiếp thu ý kiến thẩm định của Bộ Tư pháp đối với dự án Luật giá (sửa đổi) (Số: 115/BC-BTC)